Spectrophotometric Determination of Thymol in Pharmaceuticla Formulations Via Oxidative Coupling Reaction - I. Mohammad (College of Education for Pure Sciences, 2005)
A simple, rapid ans sensitive spectrophotometric method was described for the determination of thymol. The method involves the oxidative coupling reaction of thymol with p- phenylenediamine reagent by sodium metaperiodate in alkaline medium leading to the formation of violet colored product (indoaniline) of maximum absorbance (ʎmax)= 550nm). The proposed method allows the measurement of 0.4-24μg ml-1. The result obtained were both precise (RSD.) better than 2% and accurate (average recovery) 101.5% and molar absorptivity 7.45 X 103 (L.mol-1.cm-1) as well as Sandell's sensitivity 0.02 (μg cm-2). The method was successfully applied for the determination of thymol in mouth- washes and creams of pharmaceutical preparation and the results were in good agreement with the certified values and standard method. The common excipients used as additives in pharmaceutical do not interfere in the proposed method.